Asālību al Amri wa al Nahwi li ’Aḥādīṡi al Nikāḥi fī Kitābi Bulughi al Marāmi: Dirāsatun Taḥlīliyyatun fī ‘Ilmi al Ma’ānī - Cahyadi, Agustian Harly; Yusuf, Muhammad (Jurusan Bahasa dan Sastra Arab Fakultas Adab dan Humaniora UIN Sulthan Thaha Saifuddin Jambi, 2023)
Hadith are words, deeds, decisions that are based on the Prophet Muhammad SAW. If we want to understand a hadith, we must understand various kinds of knowledge, one of which is the science of Balaghah which includes commands and prohibitions. The author finds many words